The representation of the Orang Asli community in a Malaysian Media - Alagappar, P.N.; David, M.K.; Gan, K.H. (2010)
This study examine the representation of the Orang Asli in the New Straits Times (a local English daily) and determines the themes in this daily regarding this community firstly, 35 years after independence i.e.in the year 1992 and secondly 16 years later in 2008 that is 51 years after independence with a view to determining if the representation of the community had undergone change. The theoretical framework provided by agenda setting serves as the basis for analyzing the data. The findings reveal that the positioning and representation of the community did not undergo any change over the two time frames.